Pelaksanaan Supervisi Pendidikan oleh Pengawas di Sekolah Dasar Se Kecamatan Tengaran Kabupaten Semarang - ., Maryadi (MAJALAH ILMIAH LONTAR, 2009)
Abstract: This research aimed to know the implantation by supervision in the elementary school that the scope of supervision, the time of implementation, the of supervision, the instrument and the supervisorâs difficulties. The results of this research are expected to be useful for the development in the field of educational supervision and give some insight for elementary school supervisor for the improvement of quality of educational supervision elementation in the elementary school. Â Â Â Â Â The research used descriptive quantitative approach. The population in the research consists of 94 people. That is 6 supervisor as a main subject, 25 school principlas of elementary school and 73 teachers of elementary school in all kecamatan Tengaran as cross check. The data collection method used questionnaires in the form of check list (â), dived questionnaires and documentation. The data analysis technique used was descriptive quantitative analysis with percentage. The result showed that : 1) The scope of supervision covered a) The curriculum management and technique and procedure (70%), b) to evaluate studentsâ score achievement, the (90%), c) the arrangement of schedule (55%), d) the method to evaluate studentsâ score and the arrangement of evaluation (80,82%). 2). The time of implementation: the arrangement of evaluation hours without being informed before (65% headmaster of elementary school, and 64,38% teachers of elementary school). 3) The implementation: individual technique was by observing class and private interview (70% headmaster of elementary school, and 79,45% teacher of elementary school), group technique was by meeting (80% headmaster of elementary school and 84,3% teachers of elementary school, 4) the instrument were observation sheets. 5) Supervisorâs difficulties were the policy that was not compatible, the difficulties to arrange the time and so many school institution. Â Key word: The implementation of Education Supervision, Supervisor in Elementary School.